2018
DOI: 10.1017/s0033291718000144
|View full text |Cite
|
Sign up to set email alerts
|

A haplotype of the dopamine transporter gene modulates regional homogeneity, gray matter volume, and visual memory in children with attention-deficit/hyperactivity disorder

Abstract: Our findings suggest that the DAT1-related GMV alterations in the posterior cortical regions may contribute to visual memory performance in children with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 64 publications
1
24
0
Order By: Relevance
“…Although we matched the groups on age, future studies may want to explore how mentalising changes as a function of age in children with CU. An important task for future research will be to consider the role of trauma and anxiety when assessing affective responses in children with CU as recent research has found differential responses to affective stimuli in children with high levels of trauma/anxiety and high levels of CU (Meffert et al 2018 ). Finally, we only assessed boys and it will be important to see whether these difficulties extend to girls with CP/HCU.…”
Section: Limitationsmentioning
confidence: 99%
“…Although we matched the groups on age, future studies may want to explore how mentalising changes as a function of age in children with CU. An important task for future research will be to consider the role of trauma and anxiety when assessing affective responses in children with CU as recent research has found differential responses to affective stimuli in children with high levels of trauma/anxiety and high levels of CU (Meffert et al 2018 ). Finally, we only assessed boys and it will be important to see whether these difficulties extend to girls with CP/HCU.…”
Section: Limitationsmentioning
confidence: 99%
“…PG is the cortical motor area, and manages the opposite side half body to move at will. According to recent researches, this area also has relationship with depressive disorder (Li C. et al, 2018) and memory performance (Shang et al, 2018). In our study, the CU patients had decreased ReHo values in left PG, which may implicit the poor memory and black mood happened in CU.…”
Section: Discussionmentioning
confidence: 99%
“…This semi-structured interview scale is a reliable and valid instrument to assess DSM-IV child and adolescent psychiatric disorders and has been widely used in a variety of studies regarding childhood mental disorders (e.g. (Gau and Huang, 2014; Chiang et al ., 2015; Shang et al ., 2018).…”
Section: Methodsmentioning
confidence: 99%